‘Hemophagocytosis’ a small yet relevant bone marrow aspirate finding: experience of a tertiary care pediatric centre in India - Radhakrishnan, Nita; Tiwari, Neema; Singh, Savitri; Madan, Jyotsna; Nath, Devajit; Bindal, Usha; Shankar, Ravi (Asian Journal of Medical Sciences, 2021)
Backgrond: Hemophagocytosis (HS) is an interesting finding that is observed in bone marrow, lymph nodes, CSF other reticuloendothelial systems but at times is overlooked or is not incorporated in reports. Demonstration of hemophagocytosis is one criterion in the diagnosis of Hemophagocytic Lymphohistiocytosis (HLH). Aims and Objective: Hemophagocytosis as an important finding evaluated in pediatric bone marrows having different clinical diagnosis. Materials and Methods: A retrospective descriptive analysis of bone marrow aspirates of 73 patients showing any degree of hemophagocytosis [out of 440 bone marrow aspirates] retrieved from the archives of Department of Pathology during the period from May 2017 to May 2020 were included in the study. Only those cases where microscopic examination revealed hemophagocytosis(73 cases) were included in the study. Results: On analysing the data of 73 bone marrow aspirate 11 (1 Primary,10 secondary) cases were confirmed clinicopathologically as Hemophagocytic lymphohistiocytosis, 9 cases (2 metastasis, 4 infective, 1 acute leukemia, ,1 nutritional deficiency and 1 Hypocellular marrow with degenerative changes) were not suspected to have HLH clinically however showed features of increased serum ferritin >500mg/dl and bone marrow aspirate hemophagocytosis, favouring a diagnosis of secondary HLH (WHO 2004). Conclusion: We present a spectrum of differential diagnosis presenting with hemophagocytosis in pediatric population and its clinico-biochemical correlation assessing progression to HLH.